2019
DOI: 10.3390/galaxies7020043
|View full text |Cite
|
Sign up to set email alerts
|

Faraday Rotation of Extended Emission as a Probe of the Large-Scale Galactic Magnetic Field

Abstract: The Galactic magnetic field is an integral constituent of the interstellar medium (ISM), and knowledge of its structure is crucial to understanding Galactic dynamics. The Rotation Measures (RM) of extragalactic (EG) sources have been the basis of comprehensive Galactic magnetic field models. Polarised extended emission (XE) is also seen along lines of sight through the Galactic disk, and also displays the effects of Faraday rotation. Our aim is to investigate and understand the relationship between EG and XE R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…The former are being revised, and the latter can often be unreliable at low Galactic latitudes (Ma et al 2019). Ordog et al (2019), based on the revised CGPS data, showed a foreground RM ≈−115±12 rad m −2 in this direction, consistent with a smoothly decreasing trend in RM from longitudes 100°-180°. This suggests the RM of Source 1 arises largely in the Galaxy, leaving only a low contribution for RM host +RM source , certainly far lower than 10 5 rad m −2 , the RM of FRB 121102 (Michilli et al 2018).…”
Section: Is Source 1 Galactic or Extragalactic?mentioning
confidence: 82%
“…The former are being revised, and the latter can often be unreliable at low Galactic latitudes (Ma et al 2019). Ordog et al (2019), based on the revised CGPS data, showed a foreground RM ≈−115±12 rad m −2 in this direction, consistent with a smoothly decreasing trend in RM from longitudes 100°-180°. This suggests the RM of Source 1 arises largely in the Galaxy, leaving only a low contribution for RM host +RM source , certainly far lower than 10 5 rad m −2 , the RM of FRB 121102 (Michilli et al 2018).…”
Section: Is Source 1 Galactic or Extragalactic?mentioning
confidence: 82%
“…In lowlatitude cases such as this, the first Faraday moment of the emission is unlikely to be an accurate proxy for RM MW . In fact, even idealized scenarios with minimal path length through the foreground and no magnetic field reversals can still produce systematic bias between the first Faraday moment of diffuse, polarized emission, and the true RM MW value (Ordog et al 2019). A larger sample of extragalactic polarized sources, including FRBs, will be helpful in identifying well-behaved regions of the sky where diffuse, polarized emission can be leveraged to better subtract the foreground RM contribution.…”
Section: Implications Of Rm Valuesmentioning
confidence: 99%
“…This includes both studies of large scale structure in the Galactic magnetic field (Jaffe 2019) as well as studies of magnetism in smaller scale objects (e.g., Tahani et al 2018). Our catalog has already contributed significantly to several such studies (Ordog et al 2019;Ma et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The region of positive RMs around = 75 • , b = +4 • may be associated with the low-longitude side of Cygnus X or may be associated with the positive RMs found at lower longitudes. A study of compact source RMs and a comparison with the RM of extended emission (as in Ordog et al 2019) would contribute to understanding this region.…”
Section: Localized Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation